2016
DOI: 10.1038/srep23276
|View full text |Cite
|
Sign up to set email alerts
|

Pt-free carbon-based fuel cell catalyst prepared from spherical polyimide for enhanced oxygen diffusion

Abstract: The development of a non-precious metal (NPM) fuel cell catalyst is extremely important to achieve globalization of polymer electrolyte fuel cells due to the cost and scarcity of platinum. Here, we report on a NPM cathode catalyst prepared by the pyrolysis of spherical polyimide nanoparticles that contain small amounts of Fe additive. 60 nm diameter Fe-containing polyimide nanoparticles were successfully synthesized by the precipitation polymerization of pyromellitic acid dianhydride and 1,3,5-tris(4-aminophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…These experimental results suggest that the majority of Fe species in these samples are metallic iron and iron carbide in particle form, but we cannot exclude that the possibility of FeN x type structure to exist, since small amount of such structure has been reported in the samples prepared from a similar pyrolysis procedure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental results suggest that the majority of Fe species in these samples are metallic iron and iron carbide in particle form, but we cannot exclude that the possibility of FeN x type structure to exist, since small amount of such structure has been reported in the samples prepared from a similar pyrolysis procedure …”
Section: Resultsmentioning
confidence: 99%
“…Especially, the development of ORR over non‐precious‐metal (NPM) catalysts is strongly desired . Since Jasinski discovered the catalytic activity of cobalt phthalocyanine for the ORR and Jahnke et al reported the heat treatment of cobalt dibenzotetraazaannulene (CoTAA), numerous attempts have been made to develop NPM cathode catalysts by the pyrolysis of precursors that contain transition metals (mainly Fe or Co), a nitrogen source, and a carbon source . Promising fuel cell performance has been reported for several NPM catalysts; however, the majority of these reports involved the use of pure oxygen for the cathode gas.…”
Section: Introductionmentioning
confidence: 99%
“…Surface metallization has attracted great interest for its significant contribution to optics, electrical engineering, magnetism, and chemical catalysis [ 11 , 12 , 13 ]. Surface metallization is particularly attractive for PI materials as the precursor poly(amic acid) (PAA) contains active carboxyl sites and is highly reactive, thereby enabling facile functionalization [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was probably because the low molecular weight of the polyimide led to decreased thermal stability, resulting in the fusion of polyimide nanoparticles. To address this concern, ODA was replaced with a tri-amine monomer, 1,3,5-tris(4-aminophenyl) benzene (TAPB), to afford higher thermal stability via cross-linking (Figure 4b) [45]. Fe(acac) 3 was chosen as the Fe source for the above-mentioned polyimide nanoparticles because of its solubility in organic solvents.…”
Section: Synthesis Of Polyimide Nano-particlesmentioning
confidence: 99%